Involvement of GPX4 in irisin's protection against ischemia reperfusion‐induced acute kidney injury. Issue 2 (24th June 2020) - Zhang, Jia; Bi, Jianbin; Ren, Yifan; Du, Zhaoqing; Li, Teng; Wang, Tao; Zhang, Lin; Wang, Mengzhou; Wei, Shasha; Lv, Yi; Wu, Rongqian
Abstract: Ischemia reperfusion (I/R)‐induced acute kidney injury (AKI) is a common and serious condition. Irisin, an exercise‐induced hormone, improves mitochondrial function and reduces reactive oxygen species (ROS) production. Glutathione peroxidase 4 (GPX4) is a key regulator of ferroptosis and its inactivation aggravates renal I/R injury by inducing ROS production. However, the effect of irisin on GPX4 and I/R‐induced AKI is still unknown. To study this, male adult mice were subjected to renal I/R by occluding bilateral renal hilum for 30 min, which was followed by 24 hr reperfusion. Our results showed serum irisin levels were decreased in renal I/R mice. Irisin (250 μg/kg) treatment alleviated renal injury, downregulated inflammatory response, improved mitochondrial function, and reduced ER stress and oxidative stress after renal I/R, which were associated with upregulation of GPX4. Treated with RSL3 (a GPX4 inhibitor) abolished irisin's protective effect. Thus, irisin attenuates I/R‐induced AKI through upregulating GPX4. Abstract : 1. Production of excessive reactive oxygen species (ROS) is considered to be the most common physiological change in renal I/R. 2. Irisin improves mitochondrial function, reduces ROS production and provides organ protection in various diseases. 3. Irisin alleviate ischemia reperfusion‐induced acute kidney injury though upregulating GPX4.